2015
DOI: 10.12912/23920629/58912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glyphosate Ammonium Salt on the Bioavailable Phosphorus Content and the Activity of Selected Phosphatases in Loamy Sand

Abstract: Celem podjętych badań było określenie oddziaływania soli amonowej glifosatu na aktywność wybranych enzymów biorących udział w przemianach związków fosforu w glebie: fosfomonoesterazy kwaśnej (EC 3.1.3.2), fosfomonoesterazy alkalicznej (EC 3.1.3.1), fosfotriesterazy (EC 3.1.5.1), pirofosfatazy nieorganicznej (EC 3.1.6.1) oraz zawartości fosforu, w formie przyswajalnej dla roślin. Do badań laboratoryjnych użyto glebę zaliczaną do piasku gliniastego o zawartości węgla organicznego 8,7 g•kg-1. Do gleby wprowadzono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…Tejada (2009) reported that the effect of glyphosate on phosphatases is higher in sandy soil than in clay soil. The results are in agreement with our previous study (Płatkowski and Telesiński 2015b). According to Franz et al (1997) the phosphate group in glyphosate readily adsorbs to clay, aluminium and iron oxides in soil.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Tejada (2009) reported that the effect of glyphosate on phosphatases is higher in sandy soil than in clay soil. The results are in agreement with our previous study (Płatkowski and Telesiński 2015b). According to Franz et al (1997) the phosphate group in glyphosate readily adsorbs to clay, aluminium and iron oxides in soil.…”
Section: Resultssupporting
confidence: 93%
“…6: 286-292 doi: 10.17221/673/2015-PSE tive to the presence of glyphosate (Table 1). This is similar to our previous research in sandy soil (Płatkowski and Telesiński 2015b). The greatest effect on phosphatase activities in soil was observed after the application of Roundup 360 SL (containing glyphosate isopropylamine salt), but the presence of polyethoxylated tallow amine causes glyphosate toxicity increase.…”
supporting
confidence: 91%